Antimicrobial Susceptibility Profiles To Predict the Presence of Carbapenemase Genes among Carbapenem-Resistant Pseudomonas aeruginosa Isolates - Vallabhaneni, Snigdha (J Clin Microbiol, 2021)
Detection of carbapenem-resistant Pseudomonas aeruginosa (CRPA) with carbapenemase-producing (CP) genes is critical for preventing transmission. Our objective was to assess whether certain antimicrobial susceptibility testing (AST) profiles can efficiently identify CP-CRPA. We defined CRPA as P. aeruginosa with imipenem or meropenem MICs of ≥8 μg/ml; CP-CRPA was CRPA with CP genes (bla(KPC)/bla(IMP)/bla(NDM)/bla(OXA-48)/bla(VIM)). We assessed the sensitivity and specificity of AST profiles to detect CP-CRPA among CRPA isolates collected by CDC’s Antibiotic Resistance Laboratory Network (AR Lab Network) and the Emerging Infections Program (EIP) during 2017 to 2019. Three percent (195/6,192) of AR Lab Network CRPA isolates were CP-CRPA. Among CRPA isolates, adding not susceptible (NS) to cefepime or ceftazidime to the definition had 91% sensitivity and 50% specificity for identifying CP-CRPA; adding NS to ceftolozane-tazobactam had 100% sensitivity and 86% specificity. Of 965 EIP CRPA isolates evaluated for CP genes, 7 were identified as CP-CRPA; 6 of the 7 were NS to cefepime and ceftazidime, and all 7 were NS to ceftolozane-tazobactam. Among 4,182 EIP isolates, clinical laboratory AST results were available for 96% of them for cefepime, 80% for ceftazidime, and 4% for ceftolozane-tazobactam. The number of CRPA isolates needed to test (NNT) to identify one CP-CRPA isolate decreased from 138 to 64 if the definition of NS to cefepime or ceftazidime was used and to 7 with NS to ceftolozane-tazobactam. Adding not susceptible to cefepime or ceftazidime to CRPA carbapenemase testing criteria would reduce the NNT by half and can be implemented in most clinical laboratories; adding not susceptible to ceftolozane-tazobactam could be even more predictive once AST for this drug is more widely available.